Helping Patients Simplify and Safely Use Complex Prescription Regimens - Wolf, Michael S. (2011)
BACKGROUND: There is considerable variability in the manner in which prescriptions are written by physicians and transcribed by pharmacists, resulting in patient misunderstanding of label instructions. A ‘universal medication schedule’ (UMS) was recently proposed for standardizing prescribing practices to four daily time intervals thereby helping patients simplify and safely use their medicine. We investigated whether patients consolidate their medications, or if there is evidence of unnecessary regimen complexity that would support standardization. METHODS: Structured interviews were conducted with 464 adults ages 55–74 who were receiving care at either an academic general medicine practice or one of three federally qualified health centers in Chicago, Illinois. Subjects were given a hypothetical, seven-drug medication regimen and asked to demonstrate how and when they would take all of the medicine in a 24-hour period. The regimen could be consolidated into four dosing episodes per day. The primary outcome was the number of times per day individuals would take medicine. Root causes for patients complicating the regimen (> four times a day) were examined. RESULTS: Participants on average identified six times in 24 hours to take the seven drugs (SD=1.8; range 3 to 14). One third (29.3%) found seven or more times per day to take their medicine, while only 14.9% organized the regimen into four or fewer times a day. In multivariable analysis, low literacy was an independent predictor of more times per day for dosing out the regimen (β=0.67; 95% Confidence Interval 0.12 to 1.22, p=0.018). Instructions for two of the drugs were identical, yet 31% of patients did not dose these medicines at the same time. Another set of drugs had similar instructions with the primary exception of one having the added instruction to take “with food and water”. Half (49.5%) of participants dosed these medicines at different times. When medicines had variable expressions of the same dose frequency (“every 12 hours” vs. “twice daily”), 79.0% did not consolidate the medicines. CONCLUSION: Many patients, especially those with limited literacy, do not consolidate prescription regimens in the most efficient manner, which could impede adherence. Standardized instructions proposed with the UMS and other task-centered strategies could potentially help patients routinely organize and take medication regimens.